Just peace : how wars should end - Fixdal, Mona. (New York : Palgrave Macmillan, 2012)
"How should wars end? What outcomes are morally acceptable, and what ways of making peace should participants and observers find distasteful? Drawing on many of the wars and peaces of recent decades--wars whose muddled conduct and courses have already reshaped the political theory of warfare--this book offers a persuasive new perspective on postwar justice. It argues that wars should end in "a better state of peace," a peace stabler and more just than the one before the war began. It asks: When should a war of secession end in the founding of a new country? What is a right outcome to a war fought for territory? And what kinds of political institutions can both protect vital political rights and nourish stability once the fighting ends? This lucid and groundbreaking book explores the outer limits of the idea that it is worth paying almost any price for peace"--
Invcluded bibliographical references (p. [219]-242) and index.
Keywords: War -- Case studies; Peace -- Political aspects; Peace-building.; Politics and war; War -- Moral and ethical aspects; Strategy; POLITICAL SCIENCE / Peace; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / Political Freedom & Security / General; POLITICAL SCIENCE / International Relations / General